Peer and Reverse Mentoring: Developing PowerSkills For Multidimensional Learners. The Future of Work is multidimensional learning that accelerates skill development - J. Isabella Johnston (E4C, Employers for Change, 2021)
By 2030, as many as 375 million workers globally will have to master fresh skills as their current jobs evolve alongside the rise of automation and AI-capable machines (IBM, 2019). The impact of the 2020 - 2021 COVID-19 pandemic dramatically altered internship opportunities as well as disrupted how we gather for work. A new workplace emerged which included remote and distance internships, accelerated advancements in automation, the lack of experiential opportunities, and increased trends in skills based hiring. Many organizations do not understand, encourage, and use effective techniques like mentoring in training and developing employees. It is not surprising that only 35% of corporations feel new recruits and students are well-prepared with both technical and PowerSkills (aka soft skills) to perform at a high level in a competitivity professional environment (IBM, 2019). Literature findings support the value of mentoring to the mentee but not the mentor and the organization at large. New research in a case study of Nottingham University states that employees should be mentored so that personal development of the mentee, mentor, and organizational effectiveness and efficiency would be enhanced (Dugguh & Galadanchi, 2014). To create an inclusive and vibrant economy, we must address the disconnect between what is taught in schools and the skills employers are seeking in their new hires. This is true for workers of all ages and experiences who seek new jobs through their careers (IBM, 2019). This report seeks to give an overview of peer and reverse mentoring and examine its effectiveness and efficiency as an alternative technique to upskill both the mentor and mentee and the organization at large. The future of learning is a shared responsibility; and both public and private employer sectors need to be responsible, engaged, and proactive to create next gen experiences and learning tools that take into account multidimensions and complexities of humans that enable us to offer skills-oriented training to embrace diversity, equity, and inclusion [DEI] and creates an inclusive DEI culture of learning for all.
Keywords: 330; Peer & reverse mentoring; Multidimensional learning; Upskilling; Cognitive skill development